Long‐read genotyping with SLANG (Simple Long‐read loci Assembly of Nanopore data for Genotyping). (14th June 2022) - Dorfner, Marco; Ott, Tankred; Ott, Philipp; Oberprieler, Christoph
Abstract: Premise: Most phylogenomic library preparation methods and bioinformatic analysis tools in restriction site–associated DNA sequencing (RADseq)/genotyping‐by‐sequencing (GBS) studies are designed for use with Illumina data. The lack of alternative bioinformatic pipelines hinders the exploration of long‐read multi‐locus data from other sequencing platforms. The Simple Long‐read loci Assembly of Nanopore data for Genotyping (SLANG) pipeline enables locus assembly, orthology estimation, and single‐nucleotide polymorphism (SNP) calling using Nanopore‐sequenced multi‐locus data. Methods and Results: Two test libraries ( Leucanthemum spp., Senecio spp.; Compositae) were prepared using an amplified fragment length polymorphism (AFLP)‐based method to reduce genome complexity, then Nanopore‐sequenced, and analyzed with SLANG. We identified 704 and 448 orthologous loci with 12, 368 and 10, 048 SNPs, respectively. The constructed phylogenetic networks were identical to a GBS network produced using Leucanthemum Illumina data and were consistent with Senecio species circumscriptions based on morphology. Conclusions: SLANG identifies orthologous loci and extracts SNPs from long‐read multi‐locus Nanopore data for phylogenetic inference, population genetics, or phylogeographical studies. Combined with an AFLP‐based library preparation, SLANG provides an easily scalable, cost‐effective, and affordable alternative to Illumina‐based RADseq/GBS procedures.